Single shot laser writing with sub-nanosecond and nanosecond bursts of femtosecond pulses. Issue 1 (December 2017) - Okhrimchuk, Andrey; Fedotov, Sergey; Glebov, Ivan; Sigaev, Vladimir; Kazansky, Peter
Abstract A method is proposed for efficient laser modification of fused silica and sapphire by means of a burst of femtosecond pulses having time separation in the range 10–3000 ps. Modification enhancement with the pulse separation increase in the burst was observed on the tens picoseconds scale. It is proposed that accumulated transient tensile strain in the excitation region plays a crucial role in modification by a sub-nanosecond burst.